The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1099/ijs.0.014118-0
|View full text |Cite
|
Sign up to set email alerts
|

Listeria marthii sp. nov., isolated from the natural environment, Finger Lakes National Forest

Abstract: Four isolates (FSL S4-120 T , FSL S4-696, FSL S4-710, and FSL S4-965) of Gram-positive, motile, facultatively anaerobic, non-spore-forming bacilli that were phenotypically similar to species of the genus Listeria were isolated from soil, standing water and flowing water samples obtained from the natural environment in the Finger Lakes National Forest, New York, USA. The four isolates were closely related to one another and were determined to be the same species by whole genome DNA-DNA hybridization studies (.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
132
0
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(146 citation statements)
references
References 40 publications
4
132
0
10
Order By: Relevance
“…5,6 These ubiquitous bacteria are commonly isolated from plants, soil and water and L. monocytogenes is capable to contaminate agriculture environments, animal feed and foods. 7 The pathogenic species L. monocytogenes causes disease in humans and animals, whereas L. ivanovii only affects animals, mainly sheep and cattle.…”
mentioning
confidence: 99%
“…5,6 These ubiquitous bacteria are commonly isolated from plants, soil and water and L. monocytogenes is capable to contaminate agriculture environments, animal feed and foods. 7 The pathogenic species L. monocytogenes causes disease in humans and animals, whereas L. ivanovii only affects animals, mainly sheep and cattle.…”
mentioning
confidence: 99%
“…Molecular sequence analysis was carried out on the original isolate from partridge 1Ab to confirm identity of the strain and to establish its relationship with other Listeria isolates. Analysis was carried out in comparison with a recent detailed analysis that described a novel species Listeria marthii (Graves et al, 2010). Sequencing and phylogenetic analysis of the partial 16S rRNA gene, as shown in Figure 3, demonstrated that the isolate is most closely related to L. monocytogenes strains including the type strain NCTC 10357.…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing and phylogenetic analysis of the partial 16S rRNA gene, as shown in Figure 3, demonstrated that the isolate is most closely related to L. monocytogenes strains including the type strain NCTC 10357. In order to obtain more phylogenetic information a more comprehensive analysis was carried out using concatenated sequences of three housekeeping genes (sigB, prs and gap) and undertaking direct comparison with previous analyses (Graves et al, 2010). As illustrated in Figure 4 these analyses provided more precise description of the isolate placing it clearly within lineage II of L. monocytogenes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations